Contradiction between the blasphemy laws in Islamic nations and the international human rights law - Dwivedi, Surendra Kumar (Riga Graduate School of Law, 2023)
This thesis explores the contradiction between blasphemy laws and international human rights law. Blasphemy laws, which involve insulting or showing disrespect towards God, have gathered significant controversy due to their tendency to curtail freedom of speech in the interest of protecting religious beliefs. Among the 71 countries that recognize blasphemy laws in their legal systems, Iran, Pakistan, and Turkey were analyzed thoroughly in the thesis. The laws in Iran and Pakistan have severe punishments for blasphemy, while Turkey's laws were less harsh and later repealed due to the concern of violation of human rights. The research explores how freedom of opinion and freedom of expression are interconnected while observing their interaction between blasphemy laws. The findings suggest that freedom of expression is not an absolute right and may be restricted under certain circumstances. However, international law also protects the right to freedom of religion, which should not be subjected to insults or contempt. The thesis further scrutinizes the responsibility to prohibit incitement to discrimination, hostility, and violence under the ICCPR. Based on these considerations, the conclusion of the thesis is that blasphemy laws should not infringe international human rights standards specifically freedom of expression, except when they come under the ambit of Article 20(2) of the ICCPR. However, there is a possibility for blasphemy laws to be modified under Article 19(3) of the ICCPR, provided that they meet the requirements of necessity, proportionality, and prescription by law. This study contributes to a nuanced understanding of the tension between blasphemy laws and international human rights. It highlights the need for careful consideration of both rights in legal and policy decisions, and emphasizes the importance of respecting the rights of individuals to freely express themselves while also recognizing the significance of protecting religious beliefs. Moreover, this research shows that blasphemy laws are not only a legal issue but a social and cultural one. It is necessary to have open and respectful dialogue between different groups with varying beliefs to reduce the prevalence of blasphemy laws in the legal systems around the world. In conclusion, this thesis suggests that there needs to be a balance between protecting religious beliefs international human right law standards. A practical solution would be to amend blasphemy laws while meeting the necessary conditions under international human rights law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Religious law; Blasphemy; Human rights; Islam; International Covenant on Civil and Political Rights